2001
DOI: 10.1161/hy1001.092640
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Prognosis and Abnormal Nocturnal Blood Pressure Falls in Older Hypertensives

Abstract: Abstract-It remains uncertain whether abnormal dipping patterns of nocturnal blood pressure influence the prognosis for stroke. We studied stroke events in 575 older Japanese patients with sustained hypertension determined by ambulatory blood pressure monitoring (without medication). They were subclassified by their nocturnal systolic blood pressure fall (97 extreme-dippers, with Ն20% nocturnal systolic blood pressure fall; 230 dippers, with Ն10% but Ͻ20% fall; 185 nondippers, with Ն0% but Ͻ10% fall; and 63 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
539
5
34

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 686 publications
(603 citation statements)
references
References 18 publications
25
539
5
34
Order By: Relevance
“…Individuals with a non-dipper pattern (reduction in nighttime SBP o10%) are at increased risk for cerebrovascular and cardiovascular complications Nocturnal dipping and endothelial function in resistant hypertension T Quinaglia et al when compared with individuals with a normal dipper profile. 16,[21][22][23][24][25][26] Previous studies have shown that patients with UCRH and CRH both have blunted nocturnal drops in SBP and DBP. 3,27 In these earlier publications, patients with RHTN have a high prevalence of nondipper pattern which contributes to an increased risk of cardiovascular events, 18 as well as a high prevalence of target organ damage at cardiac, macroand microvascular levels.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a non-dipper pattern (reduction in nighttime SBP o10%) are at increased risk for cerebrovascular and cardiovascular complications Nocturnal dipping and endothelial function in resistant hypertension T Quinaglia et al when compared with individuals with a normal dipper profile. 16,[21][22][23][24][25][26] Previous studies have shown that patients with UCRH and CRH both have blunted nocturnal drops in SBP and DBP. 3,27 In these earlier publications, patients with RHTN have a high prevalence of nondipper pattern which contributes to an increased risk of cardiovascular events, 18 as well as a high prevalence of target organ damage at cardiac, macroand microvascular levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous data indicated that among older hypertensive patients (n¼575, mean age 72 years), subjects with reverse dipping (n¼63, 11%) had the highest incidence of stroke (22% during 41 months of follow-up), in particular fatal type stroke ( Figure 3) and hemorrhagic stroke; the incidence of hemorrhagic stroke was more prominent in the reverse dipping group (29% of stroke events) than in other dipping groups (7.7% of stroke events, P¼0.04). 31 The patient characteristics associated with reverse dipping are older, male and lean. In another study of treated older hypertensive patients (mean age, 76 years; n¼148), blunted nocturnal BP dipping was associated with poor physical function and cognitive dysfunction.…”
Section: Nocturnal Bp Dipping and Cardiovascular Riskmentioning
confidence: 99%
“…27,31,[33][34][35] Extreme dipping is a complex phenomenon. Contrary to the established notion that subjects with low nocturnal BP are at low cardiovascular risk, extreme dippers have a higher prevalence of silent cerebral infarction, deep white matter lesions and silent myocardial ischemia during sleep than dippers.…”
Section: Nocturnal Blood Pressure and Cardiovascular Risk Y Yano And mentioning
confidence: 99%
“…Non‐dippers and extreme dippers are defined as those with a night‐time BP reduction of <10 or >20% of daytime BP, respectively. Risers have night‐time BP levels that are higher than daytime levels5, 6.…”
Section: Methodsmentioning
confidence: 99%